Vitamin D in children with cystic fibrosis. Issue 11 (4th August 2012) - Brodlie, Malcolm; Orchard, William A; Reeks, Gordon A; Pattman, Stewart; McCabe, Helen; O'Brien, Christopher J; Thomas, Matthew F; Spencer, David Anthony
Abstract : Purpose: The Cystic Fibrosis Trust in 2007 published a recommended target of 75-150 nmol/L for 25-hydroxyvitamin D (25-OHD). In 2008 we found that only 10% of pancreatic insufficient (PI) children met this target. An increase in supplementation was implemented and a repeat audit performed in 2010. Methods: PI children ≥1 year under sole-care in our regional centre were included. Vitamin D3 supplementation increased by >450% to either 3800 IU/day liquid or 800 IU daily plus 20, 000 IU weekly tablets. In 2010 pancreatic sufficient (PS) children were also audited separately. Results: The median 25-OHD level increased from 51.5 nmol/L in 2008 (n=78, 10% >75 nmol/L) to 72 nmol/L in 2010 (n=72, 51% >75 nmol/L), p<0.0001. In PS children (n=15 in 2010) 87% had 25-OHD levels <75 nmol/L. Conclusions: A substantial increase in supplementation led to a significant increase in 25-OHD levels but around half still failed to reach the recommended target.